“Unstoppable!”: Children as Readers and Researchers of Reading in an Arts‑Based Project - Fuller, Danielle (Mémoires du livre / Studies in Book Culture, 2022)
Historians of children’s reading highlight how the voices, opinions and ideas of actual children, are missing from most institutional archives. Contemporary scholars have an opportunity to change that situation for the future by co‑producing research with children. This paper examines how a class of ten‑year‑old schoolchildren in England engaged with a multidisciplinary arts project involving creative writing, digital game‑making and reading research activities. The paper builds upon scholarship that emphasizes the importance of conceptualizing research projects about children’s reading with reference to transliteracies, multimodality and creative reading. It argues that, by offering the children different forms and media of expression and various means of documentation, the project enabled them to articulate vernacular as well as schooled ways of reading. Significantly, the children’s perspectives on their own reading acts and habits offer valuable insights into the qualities of their reading experiences as child readers navigating a twenty‑first‑century transmedia environment.